2020
DOI: 10.3390/su12197903
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Sustainable Concrete with the Use of Alternative Aggregates: A Review

Abstract: The concrete industry is a core element of the building sector, but it has to deal with the increasing attention on the environmental issues related to the production process: increasing energy efficiency and the adoption of alternative fuels or raw materials represent the most relevant solutions. The present work analyses physical, mechanical, and environmental performances of concrete incorporating residues derived from four main sources (construction and demolition waste, residues from waste treatment, meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 105 publications
(156 reference statements)
0
26
0
3
Order By: Relevance
“…Some research has shown that the use of recycled aggregate in concrete not only has social benefits but also creates a sustainable concrete structure. Sustainability factors include conserving energy and natural resources, reducing adverse effects on the environment, saving construction costs, reducing waste storage space [6][7][8]. Recycled aggregates are produced by separating degraded concrete parts from other unwanted materials and crushing them with appropriate grading [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some research has shown that the use of recycled aggregate in concrete not only has social benefits but also creates a sustainable concrete structure. Sustainability factors include conserving energy and natural resources, reducing adverse effects on the environment, saving construction costs, reducing waste storage space [6][7][8]. Recycled aggregates are produced by separating degraded concrete parts from other unwanted materials and crushing them with appropriate grading [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many materials were used in concrete pavement as alternatives for cementitious binders, such as fly ash and geopolymers and recycled aggregates and rubber as alternatives for virgin aggregate [23][24][25][26][27][28][29]. Moreover, glass waste was one of the materials that was widely used as an alternative for both cement and aggregate in concrete [30][31][32][33][34]. In addition, glass waste was implemented as an eco-alternative to aggregates in asphalt mixtures in most of the flexible pavement layers, especially in the lower, coarser layers [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…A standard concrete mix is composed of approx. 80–85% of natural raw aggregate depending on the targeted material characteristics [ 45 ]. With the global use of concrete amounting up to 20 billion tons annually [ 46 ], consumption of aggregate could be around 16 to 17 billion tons.…”
Section: Introductionmentioning
confidence: 99%